1997
DOI: 10.1007/s002130050326
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of sucrose and ethanol intake by SR 141716, an antagonist of central cannabinoid (CB1) receptors

Abstract: SR 141716, a selective central CB1 cannabinoid receptor antagonist, markedly and selectively reduces sucrose feeding and drinking as well as neuropeptide Y-induced sucrose drinking in rats. SR 141716 also decreases ethanol consumption in C57BL/6 mice. In contrast, blockade of CB1 receptors only marginally affects regular chow intake or water drinking. The active doses of SR 141716 (0.3-3 mg/kg) are in the range known to antagonize the characteristic effects induced by cannabinoid receptor agonists. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
419
1
9

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 567 publications
(457 citation statements)
references
References 11 publications
28
419
1
9
Order By: Relevance
“…The lack of effects of rimonabant on the inactive lever presses is of limited use in providing a conclusive control for motor artifacts because of the low response rates. However, at this dose, the drug did not produce any gross behavioral effects (Arnone et al, 1997), suggesting that the reduction of conditioned responding did not result from nonspecific (motor) deleterious effects. In addition, it has been reported that rimonabant did not affect operant responding for food (Navarro et al, 2001), or a 10% sucrose solution (De Vries et al, 2001) or cocaine injections (Fattore et al, 1999), suggesting that it did not affect the reward system per se.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The lack of effects of rimonabant on the inactive lever presses is of limited use in providing a conclusive control for motor artifacts because of the low response rates. However, at this dose, the drug did not produce any gross behavioral effects (Arnone et al, 1997), suggesting that the reduction of conditioned responding did not result from nonspecific (motor) deleterious effects. In addition, it has been reported that rimonabant did not affect operant responding for food (Navarro et al, 2001), or a 10% sucrose solution (De Vries et al, 2001) or cocaine injections (Fattore et al, 1999), suggesting that it did not affect the reward system per se.…”
Section: Discussionmentioning
confidence: 76%
“…Pretreatment with the cannabinoid CB 1 receptor antagonist rimonabant (SR141716; Rinaldi-Carmona et al, 1994) reduced nicotine, ethanol, methamphetamine, and morphine self-administration in rodents (Arnone et al, 1997;Navarro et al, 2001;Cohen et al, 2002;Vinklerova et al, 2002). Rimonabant also blocked the acquisition of conditioned place preference induced by morphine and cocaine (Chaperon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…11,[23][24][25] Although the molecular basis and cellular basis for the action of inverse agonists have been well documented and the physiological endpoints are well defined, the detailed physiological mechanisms through which modulation of CB1R translate to changes in peripheral tissue metabolism can be difficult to dissect. The following sections will address the physiological MOA related to the site of action for inverse agonists and the physiological pathways involved.…”
Section: Molecular and Cellular Moamentioning
confidence: 99%
“…72,73 In addition, food intake studies showed that rimonabant inhibited the intake of both regular chow or palatable food. 24,74,75 Tetrahydrocannabinol (THC) has also been shown to stimulate the intake of either chow or highfat sweetened diet. 76 These data generally support a model in which CB1R inverse agonists reduce the intake of all macronutrients with no selectivity related to palatability.…”
Section: Do Cb1r Agents Produce Weight Loss-independent Effects?mentioning
confidence: 99%
“…Anandamide is capable of increasing food intake in rats [87], while the antagonist SR-141716A inhibits the intake of food [88][89][90] and is currently being evaluated as an anti-obesity treatment with good results (see below). The underlying circuitry responsible for the therapeutic efficacy of cannabinoids in stimulating appetite is not yet known, although it is probably related to the fact that the CB1 receptor, anandamide, and 2-AG are present in the hypothalamus, which is known to be associated with feeding [91].…”
Section: Appetitementioning
confidence: 99%